Pengaruh Kombinasi Pupuk Organik Hayati dan Pupuk Anorganik Terhadap Pertumbuhan dan Hasil Jagung Manis (Zea mays L. Saccharata sturt) MS-Unsika di Sumedang - Santi, Nurul Hikmah fitria; Syafi'i, Muhammad; Rianti, Winda; Bahruzin, Bahruzin (UNIVERSITAS LABUHANBATU, 2023)
Fertilization is an important component in plant cultivation. The use of a combination of biological organic fertilizers and inorganic fertilizers can show more optimal results for soil and plants. Biological organic fertilizers contain organic matter and functional microorganisms that are good for plant growth and development. This study aims to obtain the best doses of biological organic fertilizers and inorganic fertilizers that are able to provide the highest growth and yield of sweet corn (Zea mays L. saccharata Sturt) Ms-Unsika strain. This research was conducted in Tanjungsari District, Sumedang Regency, from December 2021 to March 2022. The research method used a Single Factor Randomized Block Design (RBD) which was repeated 5 times. The treatments tested were: P1 (NPK 300 kg/ha + Urea 200 kg/ha), P2 (POH 7 cube/ha) P3 (POH 7 cube/ha and NPK 150 kg/ha + Urea 100 kg/ha), P4 (POH 7 cube/ha and NPK 75 kg/ha + Urea 50 kg/ha), and P5 (POH 10 cube/ha). The results of this study showed that the application of biological organic fertilizers and inorganic fertilizers had a significant effect on the growth and yield of sweet corn in the P3 treatment (POH 7 cube/ha and NPK 150 kg/ha + Urea 100 kg/ha) showed the best results on plant height parameters, stem diameter, number of leaves, cob length, cob weight with cob and cob weight without cob.